Ways to maximize the triple bottom line of the telecommunication industry in Malaysia - Wahid, N.K.A.; Mustamil, N.M. (Emerald, 2017)
Purpose: The purpose of this paper is to examine the potentials of spiritual leadership in maximizing the triple bottom line (TBL) (people, planet, and the profit) of the telecommunication industry in Malaysia. The research was conducted as a quantitative study based on the SEM Smart-PLS on four telecommunication organizations in Malaysia that represent the Malaysian telecommunication industry. The research was intended to prove that organizations can still develop a business model that adopts and adapts to spiritual, ethical, and moral leadership style as well as guarantees employees’ well-being, organizational sustainability, and social responsibility without sacrificing its profitability by acknowledging the spiritual impact on management and employees’ performance. Design/methodology/approach: The research was conducted using the spiritual leadership survey developed by Louis W. Fry (2010) called the spiritual leadership balance scorecard that measured the spiritual leadership dimensions, spiritual well-being against the measure for TBL of productivity, organizational commitment, and life satisfaction (Fry and Altman, 2013; Fry et al., 2010). A set of questionnaire was developed that combines prior established instruments, and sent to 140 employees working in the telecommunication organizations in Malaysia on a purposive sampling method, based on the SEM-PLS approach (Hair, 2010). Findings: The research has proven that organizations can still boosts its profitability by adopting to business models that acknowledge the importance of human values, the emotional part and the spiritual part. As the research has surprisingly proven that by having spiritual leaders on premise, a telecommunication provider will be able to awaken a sense that one’s life has meaning, not just to his or her own selves, but to the community at large as well. The spiritual leaders are able to influence a sense that one’s life has meaning and wanting to make differences in others life as when the employees, through the inner life, hope and faith given by the leaders in striving for the visions with altruistic love. Research limitations/implications: The limitation of the study to include cultural values as a contributing factor to the spiritual values could have been an avenue for future research on the influence of spiritual leadership on the TBL of such organizations. As such, this may be the reason why the employees of the telecommunication organizations in Malaysia are scoring low in developing a sense of calling, when due to the culture of being Malaysian, scoring high in Hofstede’s theory of culture on uncertainty avoidance and power distance (Ting and Ying, 2013). Practical implications: Adapting to spiritual leadership facilitate employee engagement by tackling the soft part of human resources, the inner sense. The inner sense is able to awaken the conscience and compassion, which can lead to effective working attitude, commitment, and engagement as reciprocal effects. Social implications: Spiritual leadership is the agenda to win back employees’ trust and confidence to the organizations which have proven to cause mishap in the current economic trend. The values brought by spiritual leadership are able to balance between work and life and in fulfilling the human needs to feel appreciated, regarded and respected and that being human, the urge to be connected to a community is unavoidable and to feel happy with what they are doing is the food for the soul. Originality/value: No study has ever been conducted in the Malaysian context with regard to spiritual leadership and at the same time employing the balance scorecard developed academically into a practical context. On the other hand, the study also proved to be the first with regard to scientifically proving the importance of spiritual values to leadership style, workplace experience as well as to organizational performance in terms of job satisfaction, productivity, and satisfaction in life.